Community pharmacists' perceptions of a hospital based virtual clinical pharmacy service: Findings from qualitative research - Lucy Bucknell; Brett Chambers; Shannon Nott; Emma Webster (Exploratory Research in Clinical and Social Pharmacy, 2024)
Background: A Virtual Clinical Pharmacy Service (VCPS) was introduced in selected rural and remote NSW hospitals in 2020 to address a gap in onsite clinical pharmacy services. Follow-up research determined hospital staff and patients at these locations perceived the service as a safe, effective and efficient system for delivering clinical pharmacy services. Community pharmacists are key stakeholders in medication safety and continuity of management in these regions, however, their insight on the VCPS had not yet been sought. Objective: To understand perspectives of community pharmacists on the implementation of VCPS in rural and remote hospitals and impacts on medication management at transitions of care. Methods: Semi-structured interviews were conducted via videoconference with seven community pharmacists with at least three months exposure to VCPS following service implementation. Thematic analysis of transcribed interviews was conducted influenced by Appreciative Inquiry. Results: Participants identified that the VCPS had supported and enhanced their community pharmacy practice and acknowledged its future potential. Identified themes were interaction with VCPS, acceptability of VCPS, community pharmacy workflow, and involvement in patient care. Suggested improvements included involving community pharmacists early in the implementation of the service and establishing clear expectations and procedures. Conclusions: The experiences of community pharmacists with VCPS were positive and there was a consensus that the introduction of the service had assisted interviewees in providing medication management to patients at transition of care. The ease of communication and efficiency of the service were recognised as key factors in the success of VCPS for community pharmacists.